Political Mobilization or Political Modernization? State Cultural Policy and Use of a Gender Resource of State Policy and Management - Lev Evgenievich Vostriakov; Marina Aleksandrovna Kashina (Управленческое консультирование)
The authors consider the usage of gender resource in the processes of political modernization and political mobilization in Russia. They conduct a comparative analysis of these processes from the point of view of their beneficiaries. The authors prove that the story of «Sveta from Ivanovo» is a good example of successful mobilization of conservative gender resource using web-technologies. It is argued the importance of the state cultural policy in the formation of modern gender relations and the authors show that modern Russian state cultural policy is aimed mostly at the conservative political mobilization. This reduces the efficiency of the use of gender resource in public administration